Beyond building: architecture through the human body - Abd. Manan, Mohd. Shahrudin; Smith, Chris L. (Faculty of Design & Architecture, Universiti Putra Malaysia, 2012)
Beyond the gestalt discourse of form and shape of tectonic buildings, the human body plays an imperative role throughout the whole process of production, exchange, and consumption of everyday architecture. Besides its objectival nature of enveloping skin, the human body as a dialectical subject becomes an epistemological dispositif in order to transcend the positivistic paradigm of architecture. Focusing on a series of critical arguments by philosophers and architectural theorists, this paper seeks to explore the contextualization of the human body as a performative critique in the production of architecture. As such, we argue that both the human body and architecture are a form of “material flow” that are made up of many machines for enunciating, which include the prosthetic body of fashion, the moving body of urbanity, and the technologized body of mediatecture. Within this field, this paper suggests the potential of transforming the way in which we envision and understand contemporary architecture, revealing new desires and possibilities for bridging interdisciplinary design research between architecture, fashion and the sociologic study of pop culture